2022
DOI: 10.4317/medoral.25092
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of DNA from human papillomavirus in patients with oral squamous cell carcinoma

Abstract: Background Survival of patients with oral squamous cell carcinoma (OSCC) is generally low, with the likelihood of locoregional recurrence or disease progression (LR/DP). Knowledge of prognostic factors for survival is key to achieving an understanding and increased survival. The present study aimed to identify prognostic factors for patients with OSCC, especially the presence of DNA from human papillomavirus (HPV). Material and Methods Retrospective cohort study includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Within the HNSCC group, patients with HPV-related OPSCC generally show significantly better therapeutic response, progression-free survival, and overall survival [6,7] compared to HPV-unrelated OPSCC. Although the impact of HPV status on the development and clinical behavior of OSCC is controversial, some studies have reported improved survival [20] and a better prognosis when associated with HPV infection [8]. Viral etiology alone is insufficient to confer favorable behavior to HNSCC [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the HNSCC group, patients with HPV-related OPSCC generally show significantly better therapeutic response, progression-free survival, and overall survival [6,7] compared to HPV-unrelated OPSCC. Although the impact of HPV status on the development and clinical behavior of OSCC is controversial, some studies have reported improved survival [20] and a better prognosis when associated with HPV infection [8]. Viral etiology alone is insufficient to confer favorable behavior to HNSCC [21].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that HPV+ OPSCC cases have a better prognosis and response to treatment compared to those negative for the virus [6,7]. However, the relevance of HPV status in OSCC is less clear, and the information is controversial [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the significance of HPV status for the survival of OSCC patients is still controversial. While high risk HPV positivity could be a good predictor of five-year survival rate of OSCC patients [8,9], another study found that HPV status had no impact on OSCC prognosis, except in patients with recurrent or progressive disease, where HPV positivity was significantly associated with improved survival compared to HPVnegative OSCC patients [10]. Emerging evidences confirm that genetic variations in immune-related signaling pathways in both tumor and immune cells play a key role in the immune landscape, and influence the antitumor immune response and tumor progression.…”
Section: Introductionmentioning
confidence: 96%